Peran Program Jaminan Sosial Sebagai Kebutuhan Dasar Masyarakat Di Indonesia Berdasaran Undang-Undang Nomor 40 Tahun 2004 - Putra, Romiansyah; Putra, Nur Rohman; Putra, Cinta Cantika D. P; Putra, Bryan Candra Kusuma; Putra, Anggun Nur Alfia (DPPM Universitas Pelita Bangsa, 2025)
Social security is a system designed to protect individuals from social risks that could threaten their well-being. Introduced in the early 20th century, the concept is increasingly relevant in Indonesia along with social, economic and globalization changes. The National Social Security System (SJSN) is regulated by Law No. 40/2004 and Law No. 24/2011, covering various programs such as the National Health Insurance (JKN), Old Age Insurance (JHT), and Work Accident Insurance (JKK). While the system aims to provide protection against risks such as sickness, accidents, and retirement, challenges such as low public participation, especially in the informal sector, as well as problems in the quality of BPJS services have been obstacles. Improvements in regulations, services, and public awareness are needed to increase the effectiveness of the social security program. With good cooperation between the government, BPJS, and the community, it is hoped that social security can improve the overall welfare and quality of life of the Indonesian people